Споменът като архив. Елка Константинова в една недовършена анкета - Александрова, Надежда (Poznańskie Studia Slawistyczne, 2020)
Elka Konstantinova is a well-known name in Poland. She has defined her work as a lecturer at the Jagiellonian University in Krakow and as a diplomat in Warsaw as an important part of her life. The text presents an unknown and unpublished survey on her memories about her work in Poland and the circumstances of preparing this unfinished survey ment to deal with the question of Konstantinova’s biography and memories.